Usage of glulam waste for particleboard production - Almeida, Tiago Hendrigo de (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2020)
Glulam are long engineered wood beams (or columns) composed by graded lumbers bounded together with the use of appropriate adhesives under pre-established pressure. The greater the industrialization the greater will be the production of wood waste a matter that deserves attention and development of technologies in terms of its waste management. This paper aimed to investigate the technical feasibility of Brazilian industrial glulam waste usage as raw material for particleboard production industries using a castor oil-based polyurethane adhesive. Particleboards were manufactured using glulam (produced with Eucalyptus urograndis) waste particles and castor oil-based polyurethane adhesive at 8, 10, 12 and 14% mass proportions and characterized based on NBR 14810-2:2006 procedures. Analysis of variance was performed for the comparison of mechanical and physical performances of the panels. The increase of adhesive content caused and increase of the MOR (Rupture Modulus), but the MOE (Elasticity Modulus) and the physical properties remained unaltered above 12% of adhesive content. The adhesive content greater than 8% provided panel performances that met the standardized specifications. Based on these findings, it was possible to conclude that the waste of glulam produced with Eucalyptus urograndis can be used as raw material for particleboard production.